Research of free radical and tissue energy supply processes on rats subjected to concurrent Tetrachlormethane and Adrenaline impact after Mexidol administration - Kateryna Aleksevych; Lydmila Fira; Oleh Hrymaluck; Angela Shtroblya (Journal of Education, Health and Sport, 2015)
Aleksevych K. O., Fira L. S., Hrymalyuk O. I., Shtroblya A. L. Research of free radical and tissue energy supply processes on rats subjected to concurrent Tetrachlormethane and Adrenaline impact after Mexidol administration. Journal of Education, Health and Sport. 2015;5(3):269-278. ISSN 2391-8306. DOI: 10.5281/zenodo.16439